Bronchiectasis as sequelae in patients with pulmonar tuberculosis - Llanos-Tejada, Felix K. (2020)
Bronchiectasis is a clinical syndrome, common in our country, as a result of a series of conditions of persistent inflammation with bronchial structural damage. Its causes are multiple, which include the pulmonary tuberculosis sequelae. In this symposium, its pathophysiology and classification are covered, with a concise explanation of the mechanisms that produce it. In the diagnostic section, it is focused on the characteristics of the imaging tests that supports its definition; also the indications of pulmonary function tests are considered. Finally, a summary of the actual treatment proposals, under scientific evidences, were pointed out.